Shirts for life and eternity in the grave of Bishop Peder Winstrup (1605-1676) - Rasmussen, Pernilla (Archaeological Textiles Review, 2022)
This article presents the investigation of two linen shirts which form part of the funerary dress of Bishop Peder Pedersen Winstrup (1605–1679), buried 1680 in Lund Cathedral, southern Sweden. When the grave was opened in 2013, it was discovered that the body had been naturally mummified, and that the funerary dress, including the linen, was well-preserved. Extant Early Modern linen garments are rare and the Winstrup shirts are an important contribution to a small corpus. The two shirts are compared to other, similar, examples. The study focuses on the materiality of the shirts and the manufacturing techniques in the context of northern European fashionable clothing culture, as well as their function and meaning as funerary garments.